Indeks Keanekaragaman Jenis Kepiting Bakau (Scylla) Di Kawasan Hutan Mangrove Desa Tatakalai Kabupaten Banggai Kepulauan - Molomban, Muliyadi; Lige, Firga Nabila; Karim, Wahyudin Abd.; Haruna, Moh. Fahri (Jurnal Biologi Babasal, 2024)
Mangrove forests are an important habitat for mangrove crabs. However, land conversion and various community activities will threaten their survival. This research aims to determine the species diversity index of mangrove crabs (Scylla) in the mangrove forest area of Tatakalai Village, Banggai Islands Regency. The research took place in the mangrove forest of Tatakalai Village, Banggai Islands Regency in June - July 2022. The samples for this research were all species of mangrove crab (Scylla) that were obtained. Sampling was taken by exploring the mangrove forest area and placing crab traps and collecting data on environmental factors. Data analysis uses the diversity index formula (H'). The results of the research found 2 types of mangrove crabs in the genus (Scylla), namely Scylla serrata and Scylla olivacea, with the diversity index of mangrove crabs (Scylla) (H') = 0.59827 belonging to the low diversity category. Environmental factors at the research location with water temperature 26?-28?, water pH 7.2-7.4, and water depth 80-175 cm. Mangrove crabs have an important ecological relationship to mangrove forests. There needs to be awareness among the people of Tatakalai Village, Banggai Islands Regency, to always preserve the environment around the mangrove forest area.